SATISFACTION OF PATIENTS AND EMPLOYEES AT TILANGO PUSKESMAS, GORONTALO REGENCY - Sylva Flora Ninta Tarigan; Tri Septian Maksum; Moh. Rivai Nakoe (International Journal of Health Science & Medical Research, 2023)
AbstractTilango Public Health Center is an inpatient health center that is located far from trans road access, so it can be a factor in the lack of patient visits. In addition, the number of employees in the inpatient unit of the Tilango Health Center is more midwives than nurses, and even doctors are only on-call (not permanent), so many people are still dissatisfied with the services of the Tilango Health Center. The purpose of the study was to determine the satisfaction of patients and employees at the Tilango Public Health Center, Gorontalo Regency. This research is included in descriptive observational research. The population is all patients and employees of the Tilango Public Health Center, totaling 43 people. The sampling technique uses total sampling so that the number of samples is the same as the total population. Data were collected using a questionnaire instrument. The data were analyzed descriptively and then narrated. The results showed that the performance of the inpatient unit at Tilango Health Center was viewed from the customer's perspective, with indicators of patient satisfaction categorized as satisfied (93.34%), while the performance of the inpatient unit at Tilango Health Center viewed from a learning perspective with employee satisfaction indicators categorized as less satisfied (26.0%). The novelty in this study is the measurement of the level of patient and employee satisfaction measured using qualitative research methods. It is recommended that the Tilango Health Center be able to improve performance and add a health service innovation process.Keywords: Satisfaction; Patients, Employees; Public Health Center